2019
DOI: 10.3892/ol.2019.10797
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of neuron‑specific enolase suppresses the proliferation and migration of NCI‑H209 cells

Abstract: Neuron-specific enolase (NSE) is generally considered as a marker for diagnosis and evaluation of the response to therapy in small cell lung cancer (SCLC). However, the role of NSE in the progression of SCLC remains to be elucidated. In the present study, the functions of NSE in SCLC, in addition to the potential mechanisms, were investigated using a loss-of-function approach with NSE-targeting small interfering (si)RNA. The knockdown of NSE markedly decreased the proliferation of NCI-H209 cells, as indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…However, the function and mechanism of NSE in SCLC were still unclear. Our previous research found that silencing NSE could inhibit the proliferation and migration of SCLC cells (13). Our clinical data also indicated that high levels of serum NSE were positively correlated with tumor metastasis in SCLC patients.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…However, the function and mechanism of NSE in SCLC were still unclear. Our previous research found that silencing NSE could inhibit the proliferation and migration of SCLC cells (13). Our clinical data also indicated that high levels of serum NSE were positively correlated with tumor metastasis in SCLC patients.…”
Section: Discussionsupporting
confidence: 66%
“…However, the effect and molecular mechanism of NSE in promoting distant metastasis of SCLC are still unclear. In addition, our previous research also found that knocking down NSE can inhibit the proliferation and migration of SCLC cells (13). Therefore, we would like to further study whether NSE can promote SCLC cell migration, invasion and distant metastasis, and to clarify its molecular mechanisms.…”
Section: Introductionmentioning
confidence: 92%
“…Liu's team silenced NSE in SCLC cell lines using a loss-of-function approach and found that the knockdown of NSE suppressed proliferation, colony formation, and migration of SCLC cells, compared to those of the control group. Also, the silencing of NSE led to the downregulation of metastasis promoter gene vascular endothelial growth factor (VEGF) and upregulation of metastasis suppressor genes NM23 and E-cadherin [44]. These experimental results may support that the elevated NSE of SCLC patients is associated with unfavorable outcome.…”
Section: Discussionmentioning
confidence: 71%
“…Measurement of plasma NSE levels has been used as a biomarker for various applications (Isgro et al, 2015). For example, it is a useful indicator of neural maturation, and is currently the most widely used biomarker for small cell lung cancer (SCLC), and it has been shown to have a direct effect in cell growth and migration in vitro on different SCLC cell lines (Zhou et al, 2011;Liu et al, 2019). Additionally, it is also used in the diagnosis and prognosis of other type of cancers as the non-small cell lung cancer (NSCLC), neuroendocrine tumors (NETs), neuroblastoma, brain cancer and brain injury (TBI) (Isgrò et al, 2015).…”
Section: Discussionmentioning
confidence: 99%